KARAKTERISTIK DAN ANALISIS FITOKIMIA TUMBUHAN OBAT DARI DESA NATAI SEDAWAK KABUPATEN SUKAMARA KALIMANTAN TENGAH : Milad Madiyawati, Fouad Fauji, I Nyoman Surasana - JHT, Admin (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2017)
ABSTRACK Patterns of community life tend to back to nature including the drugs utilization. They generally use medicinal plants (roots, stems, leaves, flowers, fruits and seeds) without knowing its active chemical compounds and partly morphologically unfamiliar also. This research was conducted to identify the characteristics of medicinal plants (general, environment, habitat and morphology of medicinal plants) through observation in the field and to know the content of active compounds (secondary metabolites) prosfective medicinal plants that be used by the community of Natai Sedawak Village by doing phytochemical testing in laboratory. Data analysis is done descriptively qualitative and quantitative in the form of tabulation and picture. The results of observation showed that the characteristics of medicinal plants in Natai Sedawak village are tree, shrub, herb (terna) and liana, with single and compound leaf composition, cylindrical trunks except tapus and Loranthus sp. They grow in swamp forest with altitude namely 17 to 25 meters above sea level and soil pH between 2.60 to 3.85. Based on the results of phytochemical analysis, medicinal plants contained secondary metabolite compounds that consisting tannin (polifenol), alkaloid, saponin, flavonoids, steroids and terpenoids that scattered in plant organs as at the roots, stems, leaves, and fruit. Keywords : Drug growth, phytochemical analysis, Natai Sedawak Village.